Cord plasma insulin and in utero exposure to ambient air pollution. (August 2017) - Madhloum, Narjes; Janssen, Bram G.; Martens, Dries S.; Saenen, Nelly D.; Bijnens, Esmée; Gyselaers, Wilfried; Penders, Joris; Vanpoucke, Charlotte; Lefebvre, Wouter; Plusquin, Michelle; Nawrot, Tim S.
Abstract: Introduction: Cardio-metabolic risk factors including insulin levels are at young age barely perceived as harmful, but over time these risk factors may track and lead to higher risk of metabolic syndrome. Studies showed that exposure to air pollution is associated with an increased risk of insulin resistance in childhood. We determined whether the origin of type 2 diabetes can be found in the early childhood by examining the levels of insulin in the neonatal cord blood and whether this can be considered as a disease marker for later life. Methods: In the ENVIR ON AGE (ENVIRonmental influence ON early AGEing) birth cohort, we recruited 620 mother-infant pairs between February 2nd 2010 until August 12th 2014 at the East-Limburg Hospital in Genk, Belgium. We investigated in 590 newborns the association between cord plasma insulin levels and exposure to particulate matter (PM2.5 and PM10 ) and nitrogen dioxide (NO2 ) in various exposure windows during pregnancy. Trimester-specific air pollutant exposure levels were estimated for each mother's home address using a spatiotemporal model. Results: Cord plasma insulin levels averaged 33.1 pmol/L (25-75th percentile: 20.1-53.5), while PM2.5 exposure during pregnancy averaged (SD) 13.7 μg/m 3 (2.4). Independent of maternal age, newborn's sex, birth weight, gestational age, parity, early-pregnancy BMI, ethnicity, smoking status, time of the day, maternal education, time of delivery, and season of delivery, cord plasma insulin levels increased with 15.8% (95% CI 7.8 to 24.4, p  < 0.0001) for each SD increment in PM2.5 levels during the entire pregnancy and was most pronounced in the 2nd trimester (13.1%, 95% CI 3.4 to 23.7, p  = 0.007) of pregnancy. The results for PM10 exposure were similar with those of PM2.5 exposure but we did not observe an association between cord blood insulin levels and NO2 exposure. Conclusions: Exposure to particulate air pollution during pregnancy is associated with increased levels of cord plasma insulin at birth. The public health relevance of this association is demonstrated by the fact that a 2.4 μg/m 3 (SD) increase in PM2.5 during pregnancy on cord plasma insulin levels corresponds to the effect-size of a 9 kg/m 2 higher early-pregnancy BMI on cord plasma. Particulate air pollution induced changes in cord plasma insulin levels during early life and might be a risk factor in the development of metabolic disease, such as glucose intolerance or type 2 diabetes, later in life. Highlights: We provide evidence for a positive association between cord plasma insulin levels and PM2.5 exposure during the early life. Pollution–induced changes in cord plasma insulin levels might be a risk factor for cardio-metabolic disease later in life. A SD increase in PM2.5 during pregnancy on cord plasma insulin levels corresponds to a pre-pregnancy 9 kg/m 2 higher BMI.